Regulação profissional ou interprofissional do trabalho em saúde?: desafios para os sistemas de saúde na Índia, Estados Unidos, França e Brasil - Rígoli, Félix Héctor (2018)
Not very long ago, the decision on getting a qualification in health, professional practice and other aspects related to a profession in the healthcare area were considered relatively stable facts of reality that depended mainly on individual decisions and possibilities. This did not mean that the State did not play some role, especially in the medical profession; in most cases, it acted as sponsor of the professional bodies. However, the growing role of health policies as public policies — added to some malpractice scandals that reached the public opinion — forced the inclusion of regulatory mechanisms as part of the functions of the State.